Evaluasi Program Dan Penilaian Hasil Pembelajaran Kurikulum Tingkat Satuan Pendidikan (Ktsp) Di Sekolah Dasar - Ina Magdalena; Deswita Sawitri; Balqis Nabila Ayu Putri; Septyana Rahmawati (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This study aims to evaluate the development and implementation of the School-Based Curriculum (KTSP) in the field. The evaluation is conducted using the CIPPO model (context, input, process, product, and outcome), which involves several aspects such as KTSP documents, the development of syllabi and lesson plans, implementation of teaching and learning, and assessment of learning outcomes. The results of the study show that the implementation of KTSP is not yet optimal due to several factors, such as the lack of socialization, guidance, and supervision from the Education Office, as well as the limited number of supervisors. Other reasons include the perception that KTSP still focuses on the knowledge dimension, limited infrastructure, financial constraints, and difficulties in meeting the requirements for smaller class groups. The evaluation of the process indicates that the preparation of KTSP documents is not yet optimal, syllabi and lesson plans do not comply with the standards, and classroom management does not meet the process standards. The assessment of learning outcomes also does not fully comply with the assessment standards, and there is a lack of teachers' understanding of assessment principles. In the assessment system, various techniques such as written tests, observation, performance tests, assignments, oral tests, portfolio assessment, self-assessment, and peer assessment can be used. The assessment principles that should be applied include validity, objectivity, fairness, integration, disclosure, comprehensiveness, continuity, systematicity, criterion-referenced testing, and accountability. The findings of this study can serve as a basis for improving the development and implementation of KTSP and enhancing the assessment system in education.